2022
DOI: 10.1002/anie.202202271
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nitrogenase Iron Protein Substituted with a Synthetic [Fe4Se4] Cluster

Abstract: The Fe protein of nitrogenase plays multiple roles in substrate reduction and cluster maturation via its redox-active [Fe 4 S 4 ] cluster. Here we report the synthesis and characterization of a water-soluble [Fe 4 Se 4 ] cluster that is used to substitute the [Fe 4 S 4 ] cluster of the Azotobacter vinelandii Fe protein (Av-NifH). Biochemical, EPR and XAS/EXAFS analyses demonstrate the ability of the [Fe 4 Se 4 ] cluster to adopt the super-reduced, all-ferrous state upon its incorporation into AvNifH. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…reported that an Fe protein with an Fe4Se4 cluster is reduced to the all ferrous state in the presence of dithionite, rendering it EPR silent in perpendicular mode EPR. 35 In this context, the signal observed in Figure 2-figure supplement 7 may correspond to the [Fe4S4] 1+ state while the [Fe4Se4] 0 state is not observed. Our results cannot distinguish between these two possible interpretations.…”
Section: Ksecn-soaking Ofmentioning
confidence: 87%
See 1 more Smart Citation
“…reported that an Fe protein with an Fe4Se4 cluster is reduced to the all ferrous state in the presence of dithionite, rendering it EPR silent in perpendicular mode EPR. 35 In this context, the signal observed in Figure 2-figure supplement 7 may correspond to the [Fe4S4] 1+ state while the [Fe4Se4] 0 state is not observed. Our results cannot distinguish between these two possible interpretations.…”
Section: Ksecn-soaking Ofmentioning
confidence: 87%
“…The exchange of selenium into an Fe 4 S 4 cluster through reaction with KSeCN represents a new approach for generating Fe 4 Se 4 -containing Fe proteins from native Fe 4 S 4 -containing proteins and a selenium source that complements existing reconstitution approaches using apoproteins (proteins deficient in the native Fe 4 S 4 cluster) and a (i) selenium source, iron source, and reductant or (ii) with synthetic clusters. 34,35 The capability of preparing chalcogenide substituted clusters opens new avenues for exploring the multiple roles of the Fe protein in biological nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made, however, toward establishing the potential physiological relevance of the all-ferrous state of the Fe protein. A recent study demonstrated that contrary to its native counterpart, a variant of the A. vinelandii NifH protein containing an [Fe 4 Se 4 ] cluster in place of the [Fe 4 S 4 ] cluster readily displayed the all-ferrous specific, g = 16.4 EPR signal in the presence of dithionite ( E 1/2 = −0.47 at 2 mM), a solution potential where the native [Fe 4 S 4 ] cluster was only capable of adopting the reduced [Fe 4 S 4 ] 1+ state [ 47 ]. This observation implies that the Fe protein could potentially access the all-ferrous state under certain physiological conditions.…”
Section: Structural and Redox Properties Of The Fe Proteinmentioning
confidence: 99%
“…However, there are clear distinctions between the functionality of NifH in catalysis and assembly. Apart from the distinctive nature of substrate reduction and cluster assembly that underlies the differences between these processes, a recent study has demonstrated the requirement of a more negative reduction potential for NifH to fulfill its function in nitrogenase catalysis than those for the same protein to carry out its functions in nitrogenase assembly [ 47 ]. Moreover, while the formation of the P-cluster involves interactions between NifH and an NifDK variant that are analogous to those between NifH and NifDK during catalysis, maturation of the M-cluster occurs on a biosynthetic scaffold that is homologous to, but clearly distinct from NifDK, and involves more chemical transformations than those occurring during the process of P-cluster maturation.…”
Section: The Multi-tasking Roles Of Fe Protein In Catalysis and Biosy...mentioning
confidence: 99%
See 1 more Smart Citation